United States : Selected Issues. (IMF Staff Country Reports; Country Report ;, 1998)
This Selected Issues paper on the United States explains the behavior of inflation and unemployment during 1997-98. The paper highlights that a simple Philips curve equation relating inflation to the unemployment gap has overpredicted inflation since 1993. The mean forecast error for 1994-97 is greater than zero by an amount equivalent to two-thirds of the standard deviation of the forecast error. The paper also examines the developments in the U.S. stock prices. Alternative approaches to social security reform are also discussed.